AN ASSESSMENT STUDY OF UNPLANNED SETTLEMENTS CASE STUDY: AL-RUWAIS DISTRICT, JEDDAH, SAUDI ARABIA - El-Shorbagy, Abdel-moniem; El-Shafie, Mervat (European Scientific Journal, ESJ, 2014)
Saudi Arabia is a large country that includes many large cities; the second largest city is Jeddah. Like many other cities worldwide, Jeddah contains significant areas that were established as unplanned settlements. According to the definition of the United Nations (UN) many of Jeddah’s unplanned settlements have been classified as slums. However, some of these unplanned settlements have strategic location near the center of Jeddah, and present great potentials as a new urban quarter. Four distinctive areas were the subject of the upgrading studies conducted by Jeddah Municipality. These are Khozam district, Bani-Malik district, Al-Boghdadiyah District, and Al-Ruwais district. This study focuses on assessing the physical condition of the built environment of Al-Ruwais district as well as to investigate the common problems of the residents such as buildings problems, infrastructure problems, and social problems. It also intends to give an overview for the suggested developing programs for the rebuilding of Al-Ruwais district by the Jeddah Municipality. The main objective of the study is to identify ways in which interventions aimed at delivering services to the low-income residents can be better designed and targeted, as well as to define set of recommendations for future unplanned settlements upgrading.